Effect of perampanel in reducing depression in patients with focal epilepsy - Min Ming; Long Chen; Jian Huang; Ying Huang; Jiali Yin (IBRO Neuroscience Reports)
Abstracts: Background: High prevalence of depression is very common in epilepsy. This study aimed to discover the effect of perampanel on depression in patients with focal epilepsy. Methods: This is a prospective observational study. We included a total of 68 patients with focal EP, which were treated with perampanel. We analyzed data before perampanel treatment and at 6 and 12 months of follow-up of the optimal dose. Using the Beck Depression Inventory-II (BDI-II) scale to evaluate depression, the Mini-Mental State Examination (MMSE) to assess the cognitive function, and the Quality of Life in Epilepsy-31 items (QOLIE-31) to estimate the quality of life of EP patients. Results: The BDI-II score improved significantly compared to before treatment and at 6 and 12 months of follow-up (P < 0.001). The mean total QOLIE-31 score significantly increased from 82.9 ± 20.4 to 88.7 ± 21.2 at the 12-month follow-up (P < 0.001). In addition, seizure control was improved significantly at 12 months: 32.1 % of patients were seizure-free, and 73.2 % were responsive. Moreover, there was statistical relationship between improvement in depression and seizure control. The MMSE score was not different before and after treatment (P > 0.05). Multiple Regression Analysis was found that annual family income, etiology, the frequency of attacks in recent years, types of ASMs and the age were the influence factors of pirampanel in reducing depression (P＜0.05). Conclusion: Perampanel reduced depression symptoms in patients with focal epilepsy, although the lack of a control group or the relatively small sample size.